Customised acoustic therapy delivered through a web‐based platform—An innovative approach to tinnitus treatment. (29th December 2022) - Connell, James Thomas; Bassiouni, Ahmed; Harrison, Ella; Laden, Stephanie; O'Brien, Sinead; Sahota, Raguwinder; Carney, A. Simon; Foreman, Andrew; Krishnan, Suren; Hodge, John‐Charles
Abstract: Objectives: Customised acoustic therapy aims to moderate the neural pathways implicated in the pathophysiology of tinnitus. This study aimed to assess the efficacy of customised acoustic therapy administered via a web‐based treatment platform. Design: Clinical trial with prospective recruitment. Fifty‐eight participants underwent 6 weeks of customised acoustic therapy. Setting: Treatment was delivered for 2 h each day using a smartphone, tablet or computer. Treatment was integrated into usual daily activities. Participants: Participants with subjective tinnitus were recruited through public and private otolaryngology clinics and electronic and print media. Main Outcomes Measured: FiveQ, a novel 5 question tinnitus questionnaire, was measured at baseline and each week of treatment. Statistical analyses, including Wilcoxon, Mann–Whitney and mixed linear regression, were used to assess treatment efficacy and identify factors associated with treatment response. Results: 39/58 participants (67.2%) had an improvement in symptom severity scores, 4 had no change (6.9%) and 15 had a decline from baseline (25.9%). Mean FiveQ scores improved by 22.9% from 40.8 (SD = 21.4) at baseline to 31.5 (SD = 21.3) following 6 weeks of treatment ( p  < 0.001). With the exception of the slight tinnitus group, all other groups (from mild to catastrophic) demonstrated a treatment response. Participants with low frequency tinnitus (<2000 Hz) had a significantly greater treatment response ( p  < 0.001). Conclusion: Customised acoustic therapy administered via a web‐based platform demonstrated encouraging efficacy. At least mild symptoms at baseline and low frequency tinnitus were associated with a greater treatment response. Customised acoustic therapy offers accessible and efficacious tinnitus treatment, however longer term clinical studies are required to confirm the observed initial benefit is maintained.